2010
DOI: 10.1080/02772248.2010.537441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproductive and developmental toxicity of cypermethrin in male albino rats

Abstract: The ever-increasing use of pesticides in the agricultural and public health has become a major cause of sterility in human and various other animals particularly in males. This study was sought to screen the toxic impacts of cypermethrin (synthetic pyrethroid) on reproduction and development. Twenty-four Wistar male rats divided into four groups were orally administered cypermethrin of daily doses 50, 75, or 100 mg kg À1 bwt per day for 45 days; and for developmental toxicity, 12 female rats were separated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
6
23
0
Order By: Relevance
“…The compromised antioxidant defence system and excessive free radicals accelerate oxidative stress, which is evident in the form of increased MDA in GLF exposure. In the previous studies, an increase in LPO caused by pesticides has been indicated (Joshi, Bansal, & Jasuja, ; Vaithinathan, Saradha, & Mathur, ). A number of advantages of RES, such as protecting spermatocytes against lipid peroxidation and increasing testicular sperm numbers and sperm motility, have been shown in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 87%
“…The compromised antioxidant defence system and excessive free radicals accelerate oxidative stress, which is evident in the form of increased MDA in GLF exposure. In the previous studies, an increase in LPO caused by pesticides has been indicated (Joshi, Bansal, & Jasuja, ; Vaithinathan, Saradha, & Mathur, ). A number of advantages of RES, such as protecting spermatocytes against lipid peroxidation and increasing testicular sperm numbers and sperm motility, have been shown in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 87%
“…Increased concentration of cholesterol in testes suggests that impairment of spermatogenesis is due to decreased androgen concentration . Further, increase in testicular acid and alkaline phosphatase activity may be the result of labialization of lysosomal system and releasing the enzyme that degenerates the tissue resulting in reduction of various micromolecules, including reduction in sperm count . From the above‐mentioned findings, it has been concluded that ligands F 1 INH and F 2 INH and their germanium(IV) complexes are potent fertility inhibitors, and addition of Me 3 or Ph 3 moiety to the ligands enhances their activity in reducing fertility.…”
Section: Resultsmentioning
confidence: 99%
“…However, little is known regarding possible toxic effects of exposure to low doses of OP compounds (Weinbroum 2004; Ceh and Majdi c 2010). The widespread use of OPs has stimulated research into the possible existence of effects related to reproductive toxicity (Joshi, Mathur, and Gulati 2007;Joshi, Bansal, and Jasuja 2011;Sharma 2012a, 2012b). This class of pesticides has resulted in a decrease in fertility of human populations (Bustos-Obreg on and Hartley 2008; Joshi and Sharma 2011;Joshi 2013a, 2013b).…”
Section: Organophosphate Insecticidesmentioning
confidence: 99%